Methodological Recommendation on the Use of Artistic Gymnastics in Physical Education Lessons of General Education Schools (Journal of Pedagogical Inventions and Practices, 2022)
this methodical recommendation is to organize the science of physical education in general education schools and to give a recommendation on the role of rhythmic gymnastics and its use in lessons in educating students to be healthy, well-rounded, fit and attractive.